The role of genetic factors in clopidogrel antiplatelet therapy - Cieślewicz, Artur Robert; Kaźmierczak, Ewa; Jabłecka, Anna (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Thienopyridine derivative antiplatelet agents play an important role in the treatment of coronary artery disease. Clopidogrel isa drug blocking action of the platelet ADP receptor (P2Y 12 ). It is applied in the form of a prodrug that requires metabolic activationby cytochrome P450 enzymes. The standard antiplatelet therapy in patients with acute coronary syndrome is based on simultaneous administration of clopidogrel and aspirin. Numerous scientific reports indicate that a diverse response to clopidogrel therapy is observed in as many as 25% of patients with acute coronary syndrome. This variation may be caused by genetic factors. Polymorphisms in CYP2C19 (one of the cytochrome P450 enzymes) and ABCB1 (gene coding P-glycoprotein which takes part in absorption of clopidogrel) are considered the most frequent genetic causes of resistance to clopidogrel therapy. Knowledge of these genotypes can be helpful in finding the patients vulnerable to less effective clopidogrel therapy and establishing an effective dose of the drug.